Matriliny transformed : family, law, and ideology in twentieth century Travancore - Saradamoni, K. (Sage ; AltaMira Press, 1999)
This book examines what matriliny, the right to live in and be maintained by their taravad (natal home, or matrilineal joint family), means to women, and how and why it changed in Travancore, an independent state till it was merged with Kerala in 1947.